Endometriosis Locations and Coexistence with other Uterine Conditions in a Bulgarian Sample of Patients - Serteva, D.; Poryazova, E.; Velikova, Ts. (American International Journal of Multidisciplinary Scientific Research, 2019)
Endometriosis is a non-tumor, estrogen-dependent, chronic gynecological disease, which is characterized by the presence of endometrial glands and stroma outside the endometrium of the uterus. Endometriosis affects between 10% and 15% of women in reproductive age. It is often associated with chronic pelvic pain and reproductive difficulties. Endometriosis can be classified as ovarian, extra-ovarian or mixed. Adenomyosis is considered, by some authors, as a separate variant of endometriosis. It is diagnosed as the presence of ectopic benign endometrial glands and stroma in the myometrium, where the minimal distance from the endometrio-myometrial junction is 2-4 mm. Our study includes 224 cases of women with endometriosis with different locations - in the myometrium (adenomyosis), in the ovaries, fallopian tubes, soft tissues and appendix as well as in combination with other conditions of the uterine body, such as endometrial carcinoma, leiomyomas, endometrial hyperplasia, polyps and atrophy and cervical cancer. There are cases of coexistence of several conditions in the same patient, and we are trying to find the reason behind this.